Konsep Pembelajaran Kontekstual di Sekolah - Kadir, Abdul (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2013)
Contextual learning is one alternative that can reduce verbal learning and theoretical. In addition, this study may provide reinforcement for comprehensive understanding of the meaning or intent of linking science students are learning with hands-on experience in real life. Through contextual learning model, the learning experience is not only the case and held when someone students are in class, but it is much more important than that is how to bring the learning experience out of the classroom, which is when he is required to respond to and solve real problems faced day-to- day. Contextual learning is ideally relate to real-world problems to the theory that will be studied or presented to the students, and students are actively to solve the problem according what he gained through experience and connected with the theory that he learned at school by his teacher. Motivation to learn directly derived from the will or ideals or even certain goals that have been owned by the students in advance, so that only the teacher directs and assists in its capacity as facilitator of learning. Students become more active because he is learning, he is experiencing, and in the end he will apply its knowledge in life.